SOOT REMOVAL SYSTEM USING ELECTROMAGNETIC WAVE HEATING FOR VEHICLE EXHAUST AFTER TREATMENT - MOHD YATIM, MUHAMMAD FARHAN (IRC, 2020)
The electromagnetic soot removal system trap particulate particles from the exhaust gas of diesel engines. The efficiency of the trap is defined by the effectiveness of the trap to filter the particles. Since the new prototype was used, the effectiveness of the soot removal system has not been ascertain. This can be done by laboratory experiment to analyze the electromagnetic soot removal system. The objective of this research focused on analyzed the electromagnetic wave soot removal system regarding gas velocity after soot trap(filter) element at various outlet opening and gas velocity with different soot particle loading in filter element. From the experiment has been done, the finding shown various outlet opening and different soot particle loading in filter element give significant different in gas velocity measured.